Bimodal behaviour of charge carriers in graphene induced by electric double layer - Tsai, Sing-Jyun (Sci Rep, 2016)
A theoretical investigation is performed into the electronic properties of graphene in the presence of liquid as a function of the contact area ratio. It is shown that the electric double layer (EDL) formed at the interface of the graphene and the liquid causes an overlap of the conduction bands and valance bands and increases the density of state (DOS) at the Fermi energy (E(F)). In other words, a greater number of charge carriers are induced for transport and the graphene changes from a semiconductor to a semimetal. In addition, it is shown that the dependence of the DOS at E(F) on the contact area ratio has a bimodal distribution which responses to the experimental observation, a pinnacle curve. The maximum number of induced carriers is expected to occur at contact area ratios of 40% and 60%. In general, the present results indicate that modulating the EDL provides an effective means of tuning the electronic properties of graphene in the presence of liquid.